Statistics and the quest for quality journalism : a study in quantitative reporting - Martinisi, Alessandro; Lugo-Ocando, Jairo (Anthem Press, 2020)
This book looks at how numbers and statistics have been used to underpin quality in news reporting. In doing so, the aim is to challenge some common assumptions about how journalists engage and use statistics in their quest for quality news. It seeks to improve our understanding about the usage of data and statistics as a primary means for the construction of social reality.